The Effect of Perceived Organization Support and Employee‎Empowerment on Job Performance through Employee‎Engagement of The State Civil Apparatus (ASN) in Regional ‎Government of The District and City of East Java Province - Hakim, Lukman (International Journal of Accounting and Economics Studies, 2025)
This study examines the impact of Perceived Organizational Support (POS) and Employee Empowerment (EE) on Job Performance ‎through Employee Engagement (EG) among State Civil Apparatus (ASN) in regional governments across East Java Province. The study ‎aims to fill a gap in understanding how these factors contribute to ASN performance in a local government context, where human resources ‎are abundant but productivity remains a significant challenge. The research utilizes a quantitative approach, with data collected ‎from ASN employees across 29 districts and 9 cities in East Java using questionnaires. The results show that both POS and EE have a ‎significant positive effect on Job Performance, indicating that higher organizational support and employee empowerment lead to improved ‎performance. However, Employee Engagement does not directly influence Job Performance, suggesting that engagement alone does not ‎guarantee better performance outcomes. The study further reveals that Employee Engagement mediates the relationship between both POS ‎and EE with Job Performance. Specifically, POS and EE have a positive effect on Employee Engagement, which in turn, enhances Job ‎Performance. These findings underscore the importance of organizational support and employee empowerment in fostering a productive ‎work environment. The results provide practical insights for local government leaders to design human resource management policies that ‎effectively leverage POS and EE to improve ASN performance, thereby contributing to better public service delivery. This research also ‎enriches the academic discourse on human resource management in the public sector, especially within the Indonesian context‎.
Keywords: East Java; Employee Empowerment; Employee Engagement; Job Performance; Local Government; Perceived Organizational Support; State ‎Civil Appa-ratus.